2016
DOI: 10.1186/s12995-016-0112-y
|View full text |Cite
|
Sign up to set email alerts
|

Stonefish envenomation of hand with impending compartment syndrome

Abstract: BackgroundMarine stings and envenomation are fairly common in Malaysia. Possible contact to various marine life occurs during diving, fishing and food handling. Even though majority of fish stings are benign, there are several venomous species such as puffer fish, scorpion fish, lionfish, stingray and stonefish that require urgent medical treatment. Stonefish is one of the most venomous fish in the world with potential fatal local and systemic toxicity effects to human.Case PresentationWe reported a case of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
12
0
3
Order By: Relevance
“…As a whole, the venom is an unstable, heat-labile, high molecular weight protein with both myotoxic and neurotoxic properties. 16 Acute manifestations are characterized by intense pain at the wound site, erythema, ecchymosis, lymphedema, and paresthesias. However, chronic symptoms of the venom manifest as slowly healing ulcers at the wound site, continuing allodynic manifestations, and joint contractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a whole, the venom is an unstable, heat-labile, high molecular weight protein with both myotoxic and neurotoxic properties. 16 Acute manifestations are characterized by intense pain at the wound site, erythema, ecchymosis, lymphedema, and paresthesias. However, chronic symptoms of the venom manifest as slowly healing ulcers at the wound site, continuing allodynic manifestations, and joint contractures.…”
Section: Discussionmentioning
confidence: 99%
“…First-line treatment of scorpaenid envenomation should include immediate immersion of the affected extremity in nonscalding hot water of up to 45°C for 30 to 90 minutes to inactivate the heat-labile components of the venom. 15-17 Grossly contaminated or infected wounds should be cultured, and the use of a special culture media for Vibrio species or acid-fast stains for marine aquatic mycobacteria should be considered. 10,18,19 Antibiotics are recommended for marine envenomation wounds of the hand or foot due to the high incidence of ulceration, necrosis, and secondary infection.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiology: Stonefish stings, including those from reef stonefish, are a common injury seen in the emergency room. They are primarily found in the coastal waters of the Indo-Pacific region, including the USA, Australia, Malaysia, Hong Kong, and Singapore [17][18][19][20][21]. Few Japanese studies of stonefish envenomation have been reported [22,23]; however, Hifumi et al recently reported 15 cases over a 5-year observation period [24] and two deaths related to stonefish envenomation have been reported in Japan [25].…”
Section: Stonefishmentioning
confidence: 99%
“…They carry their venom in venom glands and use various delivery systems, such as spines or sharp fins, barbs, spikes and fangs [2, 3]. …”
Section: Introductionmentioning
confidence: 99%